ANALISIS FAKTOR RISIKO KEJADIAN RUPTUR PERINEUM DI PUSKESMAS MADUKARA 2 KABUPATEN BANJARNEGARA - Ratih Subekti (Unit Penelitian dan Pengabdian Masyarakat, Politeknik Banjarnegara, 2021)
Perineal rupture is an injury to the birth canal that occurs at the time of the birth of the baby either using a tool or not using a tool. Perineal rupture is caused by parity, birth spacing, baby weight, improper delivery leadership, cunam extraction, vacuum extraction, instrument trauma and episiotomy. The incidence of perineal rupture based on parity was most common in primiparas, which was 62% and based on infant weight the most at weight > 3500 grams, which was 46%.The purpose of this study was to determine whether there was a relationship between parity and infant birth weight with the incidence of perineal rupture at the Madukara 2 Public Health Center, Banjarnegara Regency.The type of research used is an analytic survey with a cross sectional approach. The sampling technique was using consecutive sampling method, the sample size was 36 women giving birth.Most of the respondents were in the “multipara parity” group, which amounted to 24 respondents (66.7%). Most respondents were in the group